2014
DOI: 10.2139/ssrn.2509646
|View full text |Cite
|
Sign up to set email alerts
|

A Journey Home: What Drives How Long People Are Homeless?

Abstract: This paper uses survival analysis to model exits over time from two alternative notions of homelessness. We are unique in being able to account for time-invariant, unobserved heterogeneity. We find that duration dependence has an inverted U-shape with exit rates initially increasing (indicating positive duration dependence) and then falling. Like previous researchers, we find results consistent with negative duration dependence in models which ignore unobserved heterogeneity. Exit rates out of homelessness fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The evidence of state dependence is consistent with several prior studies, including Allgood and Warren () and Piliavin et al (), but contrasts with the findings of Cobb‐Clark et al (), who also examined the JH survey and accounted for random effects in the duration process. Cobb‐Clark et al estimated hazard models of housing insecurity spells but dropped spells that were ongoing as of the first wave because they did not know how long those spells had progressed.…”
Section: Multivariate Empirical Analysessupporting
confidence: 86%
See 2 more Smart Citations
“…The evidence of state dependence is consistent with several prior studies, including Allgood and Warren () and Piliavin et al (), but contrasts with the findings of Cobb‐Clark et al (), who also examined the JH survey and accounted for random effects in the duration process. Cobb‐Clark et al estimated hazard models of housing insecurity spells but dropped spells that were ongoing as of the first wave because they did not know how long those spells had progressed.…”
Section: Multivariate Empirical Analysessupporting
confidence: 86%
“…Other results are more surprising, especially psychological conditions and poor health reducing men's risks of housing insecurity and poor health reducing women's vulnerability to violence. Cobb‐Clark et al () also found that some bad health outcomes reduced the duration of Australians' homelessness. The estimated associations might reflect these conditions leading to prioritized social services or a more consistent provision of services (e.g., fewer requirements on the receipt of services).…”
Section: Multivariate Empirical Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly though, Cobb-Clark et al (2016) find no significant relationship between previous incarceration and the duration of homeless episodes once controlling for timeinvariant heterogeneity. However, they do not study whether ex-inmates are more likely to enter homelessness.…”
Section: Two Different Explanationsmentioning
confidence: 58%
“…Given that women are one of the fastest growing demographics among the homeless (Gaetz et al, 2016), and none of the studies included in this review reported on those of other genders, future intervention research should include those of a range of genders to explore the effectiveness of interventions for a gender diverse group. This is particularly important because the experience of homelessness is known to differ across genders (Cobb‐Clark, Herault, Scutella, & Tseng, 2016; Montgomery et al., 2017), and is likely to translate into CI experiences.…”
Section: Discussionmentioning
confidence: 99%